2021
DOI: 10.1016/j.celrep.2021.109396
|View full text |Cite
|
Sign up to set email alerts
|

α2δ-1 switches the phenotype of synaptic AMPA receptors by physically disrupting heteromeric subunit assembly

Abstract: Highlights d Nerve injury augments postsynaptic Ca 2+ -permeable AMPARs in the spinal cord via a2d-1 d a2d-1, but not a2d-2 or a2d-3, interacts directly with GluA1 and GluA2 via its C terminus d a2d-1 disrupts heteromeric, but not homomeric, assembly of GluA1 and GluA2 in the ER d Gabapentin restores assembly and synaptic expression of GluA1/GluA2 in neuropathic pain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…In the spinal cord, increased α2δ-1 protein levels inhibit GluA1/GluA2 heteromeric assembly in the ER in neuropathic pain (Li et al, 2021).…”
Section: α2δ-1diminishesglua1/glua2heteromeric Assembly In the Er In ...mentioning
confidence: 99%
“…In the spinal cord, increased α2δ-1 protein levels inhibit GluA1/GluA2 heteromeric assembly in the ER in neuropathic pain (Li et al, 2021).…”
Section: α2δ-1diminishesglua1/glua2heteromeric Assembly In the Er In ...mentioning
confidence: 99%
“…CP-AMPARs that lack the GluA2 subunit have a higher single-channel conductance than the CI-AMPARs which contain GluA2 [ 66 ]. For instance, a switch to CP-AMPAR (lacking GluA2 or containing unedited GluA2) increases neuronal excitability in the hypothalamus of hypertensive rats [ 67 ], in the hippocampus of mice with seizures [ 68 ], in spinal dorsal horn neurons of rats with inflammatory pain [ 69 , 70 ], and also in differentiated human MNs in amyotrophic lateral sclerosis model [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate NMDA receptor-mediated synaptic plasticity at the spinal cord level is crucially involved in central sensitization and neuropathic pain development. α2δ-1 (encoded by the Cacna2d1 gene), previously known as a Ca 2+ channel subunit, is expressed in neurons in the DRG, spinal dorsal horn, and various brain regions. , α2δ-1 is the binding site of gabapentinoids, the first-line treatment for neuropathic pain conditions. Both traumatic nerve injury and paclitaxel treatment cause substantial and prolonged upregulation of α2δ-1 in the DRG. , Overexpression of α2δ-1 alone at the spinal cord level causes a long-lasting neuropathic pain-like phenotype. , Conversely, genetic knockout of Cacna2d1 profoundly attenuates neuropathic pain development after nerve injury or paclitaxel treatment. Recent studies revealed that upregulated α2δ-1 can form a protein complex with NMDA receptors to increase synaptic NMDA receptor trafficking in the spinal dorsal horn and that α2δ-1-bound NMDA receptors, not voltage-activated Ca 2+ channels, mediate the analgesic effect of gabapentinoids in various animal models of neuropathic pain. , Interestingly, pain hypersensitivity induced by JNJ-26481585, an HDAC inhibitor, in naive animals is reversed by gabapentin .…”
Section: Role Of Histone Modifications In Neuropathic Painmentioning
confidence: 99%
“…75,76 Overexpression of α2δ-1 alone at the spinal cord level causes a long-lasting neuropathic pain-like phenotype. 77,78 Conversely, genetic knockout of Cacna2d1 profoundly attenuates neuropathic pain development after nerve injury or paclitaxel treatment. Recent studies revealed that upregulated α2δ-1 can form a protein complex with NMDA receptors to increase synaptic NMDA receptor trafficking in the spinal dorsal horn and that α2δ-1-bound NMDA receptors, not voltage-activated Ca 2+ channels, mediate the analgesic effect of gabapentinoids in various animal models of neuropathic pain.…”
Section: Role Of Histone Modifications Inmentioning
confidence: 99%